If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p = 4p + 4 Reorder the terms: 6p = 4 + 4p Solving 6p = 4 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 6p + -4p = 4 + 4p + -4p Combine like terms: 6p + -4p = 2p 2p = 4 + 4p + -4p Combine like terms: 4p + -4p = 0 2p = 4 + 0 2p = 4 Divide each side by '2'. p = 2 Simplifying p = 2
| 2(m-6)=18 | | 3x-12-2=x | | 0.17x+0.07(60,000-x)=5000 | | 5.62=(x^2) | | X-14-2x=16 | | u-16=48 | | 24s^2+90st+66t^2=0 | | h(t)=-4.9t^2+147 | | (2c+1)(c-5)+(c-4)(c-3)= | | 60=1(10)+b | | 60x=345 | | -5p+8=18 | | X(3.50+5.50)+6=51 | | 2x-8+7x=19 | | y=-0.0444x^2+1.3333x | | x=3.333333333+0.3333333333y | | 3x=-9y+6 | | X(3.50+5.50+6)=51 | | 9y-2-2(4y-2)= | | -24=(x+3) | | (2c-1)(c-5)+(c-4)(c-3)= | | 6x-2(x-8)=4(x+1)+8 | | 60=2(10)+b | | 0=1/3x-21/3x+2(3/2x-6) | | 3x-12=y+-2 | | 6n=-104 | | 5x-18*4x=36 | | 60=3(10)+b | | -24+4x-x=39 | | 6x-3(x+2)=9-9x+12x | | 4s*5=54 | | x+x+0.52+x+0.52+0.39=10.91 |